A novel cervical tooth wear and recession index, the cervical localisation code, and its application in the prevention and management of dentine hypersensitivity. (September 2020) - Griffith, Louise J.; Newcombe, Robert G.; Daly, Sinead; Seong, Joon; Davies, Maria; West, Nicola X.
Abstract: Objectives: To design and validate a new index to assess tooth wear (TW) in the cervical region and its association with gingival recession (GR), for use both in research studies and as resource in General Dental Practice, with focused prevention and management strategiesparticularly related to aetiology of dentine hypersensitivity provided for each Code score. Methods: Codes to reflect clinical presentations of the cervical region in health and disease recording both TW and GR were defined. Validation of the Code was undertaken by 3 trained examiners who scored buccal and lingual surfaces of eligible teeth in 42 adult healthy volunteers. Each volunteer underwent 4 identical clinical examinations, being assessed twice by the examiner who performed the first and last exam. Results: Cervical Localisation Code definitions were A: no GR, no coronal TW, B: no GR, distinct coronal TW, C: GR but no coronal TW, D: GR with distinct coronal and root TW. For validation 2073 eligible tooth surfaces were scored. There were only 57 within and 201 between examiner disagreements, the most common being between scores C and D. Conclusions: The Cervical Localisation Code was used reproducibly by three independent examiners. It will provide focussed data on the cervical region in research studies allowing the association of patient reported dietary and lifestyle factors with specific lesion types, and a tool to aid the management of clinical scenarios, specifically those that lead to dentine hypersensitivity in general dental practice. Clinical Significance: Exposure of dentine at the cervical margin by TW and/or GR often results in dentine hypersensitivity, however current TW indices do not record TW location or GR presence. The Cervical Localisation Code captures both parameters and suggests likely aetiology for dentine hypersensitivity and guide clinical management of the cervical region.